2021
DOI: 10.1111/ijcp.14487
|View full text |Cite
|
Sign up to set email alerts
|

A baseline survey of community pharmacies’ workforce, premises, services and satisfaction with medical practitioners in Jordan

Abstract: Purpose The aim of the present study was to describe the local situation in community pharmacies in Jordan by assessing the baseline resources available in terms of workforce, premises and services provided. Methods A survey was developed and administered to community pharmacists from Amman, the capital of Jordan, and Irbid, a large city in North Jordan. Results Three hundred sixty‐seven community pharmacists, 167 from Amman and 200 from Irbid, completed the surveys. The community pharmacists were mostly femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Another study conducted in Jordan indicated that CPs were willing to offer nutritional advice as a part of their overall care plan and understood the importance of taking dietary supplements into account while treating patients with certain disorders, such as diabetes. 19 An article published in British Medical Journal (2022) states that nutrition was poorly integrated into medical education, implying that more education and training in this area may be required. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Jordan indicated that CPs were willing to offer nutritional advice as a part of their overall care plan and understood the importance of taking dietary supplements into account while treating patients with certain disorders, such as diabetes. 19 An article published in British Medical Journal (2022) states that nutrition was poorly integrated into medical education, implying that more education and training in this area may be required. 20 …”
Section: Discussionmentioning
confidence: 99%